Bad Kitty joins the team - Bruel, Nick. (New York : Square Fish, an imprint of Macmillan Publishing Group, LLC, 2020)
"Will Kitty find her perfect sport? Kitty is terribly out of shape--she can barely torment Puppy without need a break to huff and puff! When Kitty's owner catches her wheezing, Kitty is told it's time to EXERCISE! It takes some serious convincing, a high-stakes competition, and a little bit of trickery, but eventually Kitty gets into the competitive spirit...albeit reluctantly. Well, what did you expect?"--Back cover.
GN490L
Decoding demand: 89 (very high) Semantic demand: 99 (very high) Syntactic demand: 70 (high) Structure demand: 87 (very high)
Accelerated Reader AR
Keywords: Bad Kitty -- (Fictitious character from Nick Bruel) -- Juvenile fiction; Cats -- Juvenile fiction; Exercise -- Juvenile fiction; Sports stories; Humorous stories